Repeated Endoscopic Submucosal Dissection for Esophageal Neoplasia Located Close to a Previous Endoscopic Submucosal Dissection Scar - Nagami, Yasuaki (Clin Transl Gastroenterol, 2020)
INTRODUCTION: Endoscopic submucosal dissection (ESD) could become a standard treatment for early stage esophageal neoplasia. Recurrence sometimes develops close to a previous ESD scar. These lesions are predictably difficult to treat with ESD because of severe fibrosis. We evaluated the clinical outcomes of ESD for esophageal neoplasia located close to a previous ESD scar. METHODS: This was a retrospective observational study in a single institution. A total of 549 consecutive patients with 927 esophageal lesions were treated with ESD. The primary outcomes were resectability and adverse events of esophageal neoplasia located close to previous ESD scars (ESD scar group) than in primary esophageal ESD (primary group). Furthermore, predictive factors of perforation were examined. RESULTS: A total of 545 primary and 29 ESD scars in consecutive patients were evaluated. En bloc and complete (R0) resection rates in the ESD scar group were lower than those in the primary group (79.3% vs 98.3%, P < 0.01 and 75.9% vs 93.4%, P < 0.01). Perforations occurred more frequently in the ESD scar group (10.3% vs 2.0%, P = 0.03). The ESD scar group was a predictive factor for perforation (odds ratio = 10.37, 95% confidence interval: 2.15–49.94, P = 0.004). There were similar results for inverse probability of treatment weighting methods (odds ratio = 6.78, 95% confidence interval: 1.40–32.98, P = 0.018). DISCUSSION: ESD for esophageal neoplasia located close to a previous ESD scar was difficult to completely resect and increased the likelihood of perforation but could be a treatment option.